Pelatihan Pengolahan Keladi Menjadi Tepung Keladi Santri Ma’had Bilal Bin Rabah - Muzakki, Muhammad; Umamah, Wulan Mafrihatul; Hikmah, Nurul; Pinasih, Sari; Matdoan, Ida; Nuryanto, Aris (Universitas Pendidikan Muhammadiyah Sorong, 2024)
In several traditional markets, many Papuan mama/mace sell taro tubers that are still raw or have not been processed into food, and housewives also only manage taro or taro by frying or steaming it. However, taro contains quite a lot of nutritional content. Therefore, society needs to optimize the use of taro in an innovative and high-value manner. Ma'had Bilal Bin Rabah is an Islamic educational institution that focuses on developing Arabic and Islamic studies in Sorong district. If you look at the curriculum that Ma'had Bilal Bin Rabah has applied to his students so far, it only focuses on cultivating a deep understanding of the Islamic religion. However, they have not paid attention to other aspects which are no less important, such as soft skills which can support students in preaching in society. Meanwhile, if you look further, parents hope that their children will not only understand religious knowledge, but will also be skilled and independent. The PKM-K team will carry out service that focuses on processing taro or taro into taro flour as a substitute for wheat flour in making cakes. Meanwhile, the method used by the service during training uses active learning. The results of this service are that the students are trained to process taro into taro flour and are trained in strategies to market this product to the public.